Big data analytics in e-government and e-democracy applications: privacy threats, implications and mitigation. (30th May 2022) - Mavriki, Paola; Karyda, Maria
Big data analytics can help governments and organisations to support democratic processes through improving efficiency, effectiveness and transparency. A growing body of research investigates privacy threats related to big data analytics, but their implications for democracy are still scarcely explored. Focusing on the democratic value of privacy, we identify privacy threats for citizens stemming from the use of big data in e-government and e-democracy applications. We analyse the challenges for e-government arguing among others that automatic decision-making may lead to discrimination compromising equality, a basic democratic value. We also explore the challenges of the privacy threats for e-democracy, arguing that decreased privacy facilitates manipulation, polarisation and disinformation. Finally, we critically examine relevant technical privacy enhancing solutions which may play a significant role in shielding democracy through allowing citizens to freely share, access and discuss information and content that is contrary to political, religious or social views of governments.